Overview of the implementation of Emergency Remote Education in the Federal Network of Professional, Scientific and Technological Education of Minas Gerais (Research, Society and Development, 2020)
The pandemic caused by the new Coronavirus in 2020 imposed severe restrictions on the normal running of schools in different countries around the world, often making it impossible to carry out teaching activities in person. In view of this, educational institutions had to adapt in order to allow teaching to be offered at a distance. The term "Emergency Remote Education - ERE" was coined by the literature as the most appropriate to define the teaching model that is being offered during the pandemic. Given the above, this research aims to understand the current scenario of the implementation of the ERE in the Federal Institutes and the Federal Center for Technological Education - CEFET, which make up the Federal Network of Professional and Technological Education of Minas Gerais, Brazil. To this end, a bibliographic and documentary review on Emergency Remote Education in the context of the pandemic was carried out, highlighting the challenges to its implementation in the country in order to provide subsidies for the definition of criteria that guarantee the quality of this offer. Then, a survey of the regulations, documents and publications made available on the portal of the researched institutions was carried out to establish a comparison between them based on the criteria previously defined. The survey found that the evaluated institutions were able to incorporate most of the criteria in order to guarantee the quality of the ERE offer. However, differences were identified in the time they were implemented and in their incorporation into the regulations.